THE SPECIFICITY AND COMPLEXITY OF THE PROCESS OF LEARNING ENGLISH - Khodjayev K.K (Research Parks Publishing LLC, 2021)
This article discusses the specificity and complexity of the process of learning English. Methodological assistance and recommendations were provided to English language learners